Successful hemodialysis catheter placement into a stenosed femoral vein using balloon dilation for central venous access - Koichi Saiki; Takuro Fujita; Yoshihiro Toyama; Tomoko Yokoyama; Masahito Yamanaka (Radiology Case Reports)
A 67-year-old woman with end-stage renal failure due to immunoglobulin A nephropathy had undergone hemodialysis for 20 years. The patient was dependent on catheterized dialysis and underwent 13 central venous catheter changes. A GlidePath catheter (Bard Medical, Georgia, USA) was placed in the right femoral vein and removed because of infection. There was no alternative but to implant the central venous catheter at the same site. Computed tomography revealed stenosis of the right external iliac vein. Therefore, balloon dilation with a Mustang balloon (5.0 mm) (Boston Scientific, Marlborough, Massachusetts, USA) was performed before central venous catheter implantation. The number of patients undergoing dialysis who require vascular access catheters is expected to increase because of the aging population and extended duration of dialysis treatments. Balloon dilation prior to catheter placement is effective in patients with vascular stenosis.